1988
DOI: 10.1007/bf01400524
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriovenous malformations (C. AVM) and associated arterial aneurysms (AA)

Abstract: We report a series of 101 patients with cerebral arteriovenous malformations (CAVM), in which 23 cases presented with one or several arterial aneurysm(s) (AA). Each AA could be classified into distal intra-lesional, proximal or remote. Patients with CAVM + AA tend to be older and more frequently present with epilepsy, haemorrhage events and neurological deficits. Of these 23 patients, 16 had their AVM treated partially or totally by embolization. In our series, the endovascular treatment of the arteriovenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(61 citation statements)
references
References 41 publications
1
57
0
3
Order By: Relevance
“…Luessenhop 16 observed that partial embolization may reduce the risk of hemorrhage by reducing intranidal pressure. However, the reports found in the literature so far are inconclusive concerning the protective role of partial embolization 7,12,16,18,23 , since any residue of malformed vessels has the potential to cause future bleeding, no matter what percentage of the lesion was obliterated 15,18,22,23 . Partial embolization has also been thought to increase the risk of cAVM rupture, even in patients without a previous hemorrhagic event 8,10 .…”
Section: A B Cmentioning
confidence: 99%
See 4 more Smart Citations
“…Luessenhop 16 observed that partial embolization may reduce the risk of hemorrhage by reducing intranidal pressure. However, the reports found in the literature so far are inconclusive concerning the protective role of partial embolization 7,12,16,18,23 , since any residue of malformed vessels has the potential to cause future bleeding, no matter what percentage of the lesion was obliterated 15,18,22,23 . Partial embolization has also been thought to increase the risk of cAVM rupture, even in patients without a previous hemorrhagic event 8,10 .…”
Section: A B Cmentioning
confidence: 99%
“…Associated aneurysms, especially intranidal, are also considered a factor of increased risk for hemorrhage in untreated cAVMs 2,12,27,28 . The occlusion of aneurysms has been thought to confer relative protection 2,12,29 .…”
Section: A B Cmentioning
confidence: 99%
See 3 more Smart Citations